Mesaolo- On the reuse of corn cobs - Freitas, L.; Brás, B. (Open Schools Journal for Open Science, 2021)
This project intends to reuse corncobs from the cultivation of corn with the use of a natural resource produced in large quantities, the resin. Thus, waste from nature is reused in order to obtain an object used by thousands of people daily, the table tops. As deforestation industrially, with the development of this project, it aims to reduce deforestation to increase environmental sustainability.